Risking another Rohingya refugee crisis in the Andaman Sea - Felix Heiduk; Antje Mißbach (Stiftung Wissenschaft und Politik (SWP), 2020)
Kutupalong - which, located near Cox's Bazar in Bangladesh, is the biggest refugee camp in the world with an estimated 700,000 inhabitants - has just witnessed its first coronavirus death. The 71-year-old victim was among at least 29 Rohingya refugees in the camp who had recently tested positive for the virus. The death of the refugee has increased concerns that the deadly virus could spread rapidly through refugee camps in Bangladesh, which are home to an estimated 1 million refugees. Observers also fear that the coronavirus outbreak could create panic in the camps and induce more Rohingya to seek refuge in Indonesia and Malaysia by crossing the Andaman Sea in boats. Malaysia and Indonesia are refusing to allow the passengers of any such boats to disembark over fears that they could be carrying the virus. According to official statements, Malaysia has turned back 22 boats since May 2020. In the second week of June, 269 Rohingya were detained in Malaysia after their vessel had reportedly been intentionally damaged, thus thwarting efforts to push it back to sea. These recent events have exacerbated fears that the current situation could turn into another Andaman Sea refugee crisis.
Keywords: 320